Meander-line-based inhomogeneous anisotropic artificial material for gain enhancement of UWB Vivaldi antenna - Pandey G.K.; Singh H.S.; Meshram M.K. (My University, 2025)
An inhomogeneous anisotropic (IA) artificial material (AM) is proposed having epsilon-near-zero (ENZ) characteristics and effective refractive index >1, simultaneously, in the same direction. Further, the proposed IA-AM is utilized for the gain enhancement of Vivaldi antenna for ultra-wideband (UWB) applications. The IA-AM consists of two types of compact meandered line-based anisotropic artificial material with ENZ characteristics in two adjacent narrow bands of 5.5–8.5 and 8–11.5 GHz. However, the non-resonant behavior of the artificial material in other direction appears with high refractive index property in broadband region. The combination of both the unit cells with broadband ENZ and high refractive index property is used to improve the gain of the Vivaldi antenna in broadband. The proposed IA-AM-loaded Vivaldi antenna exhibits a gain enhancement of up to 2 dBi compared to the original antenna in the operating frequency band of 3.1–12 GHz with |S11| < −10 dB. The proposed antenna shows nearly stable unidirectional radiation patterns with high directivity and nearly flat group delay. © 2016, Springer-Verlag Berlin Heidelberg.